Effectiveness of Implementing Limited Liability Company Legal Entity Registration Through Online Single Submission by a Notary - Dewi, Puput Shintia (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This research aims to analyze: the implementation of limited liability company legal entity registration through the OSS system by notaries in Pekanbaru City, and the effectiveness of limited liability company registration via OSS by notaries in Pekanbaru City. The approach method used is empirical/sociological and includes analytical descriptive research. Data sources were obtained through interviews conducted directly with notaries as resource persons and other literature studies. The research results showed that the registration of a limited liability company (PT) legal entity begins with the preparation of a deed of establishment of a limited liability company by a notary as an authorized official. The deed of establishment contains the company's articles of association. After the deed of establishment is issued, the business actor or notary as their representative must register a business license through the OSS system, which will then result in obtaining an NIB (Business Identification Number) as the company's identity in carrying out business activities. The effectiveness of registering a limited liability company (PT) legal entity through the OSS system by a notary in Pekanbaru City cannot yet be assessed as effective because many obstacles are still found. Some of these obstacles are the notary's lack of understanding in OSS operations, internet network problems and websites that often have errors, difficulty in getting information regarding the requested requirements and if problems occur they still have to be reported manually so it takes longer, as well as a lack of socialization or counseling from the government.